INFORMAL COMMUNICATION IMPACT ON THE PROJECT THINKING DEVELOPMENT IN THE CONTEXT OF SOCIAL PROJECT WORK - Abysova, Mariia (Proceedings of the National Aviation University Series Philosophy Cultural, 2023)
Introduction. Recently, there has been an increased interest in the communication of social projects in various spheres of the life of the state and society. The aim of the article is to analyze the role of informal communication in the development of project thinking in the context of social project work. The research tasks are to reveal the specifics of project thinking; investigate the specifics of social object projecting; to analyze the potential of informal relations for the development of project thinking aimed at the social project. Research method is interdisciplinary. Publications studying the research problem are arranged into several groups devoted to: 1) the theory of communication; 2) the analysis of the specifics of social projecting; 3) informal communications as a social phenomenon. Research results. Social project can be defined as a well-founded organization of social relations in various spheres that meets the given requirements being realized in the near or distant future. The complexity of social projects put forward special requirements for project thinking, which has normative and prospective orientation aspects. The shortcomings of a prospective orientation process is often related to the subjective factor of those who develop and implement the project. Informal communication of employees, objectively manifested in the nature and manner of their professional interaction, create opportunities for stimulating creative potential, introducing innovative solutions. Forms of manifestation of informal interorganizational communications are myths, legends, traditions, rituals, circulating rumors. Each of these manifestations is important and carries a different function. Discussion. A type of informal communication ‒ team relations ‒ seem to be promising for project work. Conclusions. The communicative structure of the project goes beyond the formal-hierarchical relations of participants and takes the characteristics of a social network that unites people involved in the project. The contribution of informal communication in projects is related to the search for non-standard, innovative solutions, since informal communications create conditions for self-regulation of processes and relationships in the team, in which it is easier for participants to exchange ideas, thoughts, and knowledge. Due to the absence of strict formalized regulations within the framework of informal communication, the creative potential of employees is revealed, as well as the approval of changes with further consolidation in the formal structure or interaction. Management of informal communication in the form of rumours, gossip, traditions, rituals, corporate myths and legends is a necessary component of the system of measures to improve the effectiveness of project interaction.